2010
DOI: 10.1016/j.toxicon.2010.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the toxin profile of Cylindrospermopsis raciborskii T3 and function of putative sulfotransferases in synthesis of sulfated and sulfonated PSP toxins

Abstract: a b s t r a c tThe toxigenic freshwater cyanobacterium Cylindrospermopsis raciborskii T3 has been used as a model to study and elucidate the biosynthetic pathway of tetrahydropurine neurotoxins associated with paralytic shellfish poisoning (PSP). There are nevertheless several inconsistencies and contradictions in the toxin profile of this strain as published by different research groups, and claimed to include carbamoyl (STX, NEO, GTX2/3), decarbamoyl (dcSTX), and N-sulfocarbamoyl (C1/2, B1) derivatives. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…This strain was isolated from a toxic cyanobacterial bloom in Brazil (19) and has been maintained in the culture collection of the Laboratory of Cyanobacterial Ecophysiology and Toxicology (UFRJ, Brazil). The T3 strain produces STX, neosaxitoxin (NSTX) and decarbamoyl-NSTX and has been used as a type strain to elucidate the biosynthetic pathway of paralytic shellfish toxins (PSTs) (18,36). Non-axenic batch cultures of this strain were maintained in ASM-1 medium (15) at 24 ± 2 ºC, with a 12 hour L:D cycle and photon flux of 50 µmol photons.m -2 .s -1 (provided by common day light fluorescent lamps).…”
Section: Methods Strain Maintenancementioning
confidence: 99%
See 2 more Smart Citations
“…This strain was isolated from a toxic cyanobacterial bloom in Brazil (19) and has been maintained in the culture collection of the Laboratory of Cyanobacterial Ecophysiology and Toxicology (UFRJ, Brazil). The T3 strain produces STX, neosaxitoxin (NSTX) and decarbamoyl-NSTX and has been used as a type strain to elucidate the biosynthetic pathway of paralytic shellfish toxins (PSTs) (18,36). Non-axenic batch cultures of this strain were maintained in ASM-1 medium (15) at 24 ± 2 ºC, with a 12 hour L:D cycle and photon flux of 50 µmol photons.m -2 .s -1 (provided by common day light fluorescent lamps).…”
Section: Methods Strain Maintenancementioning
confidence: 99%
“…The PST profile of C. raciborskii T3 is STX, NSTX and dcNSTX (36). Here, we measured PST production as the sum of STX and NSTX only, since we had no dcNSTX standard available.…”
Section: Pst Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatic analyses of Kellmann et al [149] indicated that the synthesis of STX begun with the multifunctional polyketide biosynthesis enzyme ( SxtA ). Only a few studies are evident about STX genes; to date STX biosynthetic gene cluster has been reported from five genera of cyanobacteria [107,108,149,150,151] and 33 genes involved in STX biosynthesis, transport and regulation were also reported in their study. The size of these gene clusters was 25.7 kb ( Raphidiopsis brookii D9) to 36 kb ( Lyngbya wollei ).…”
Section: Saxitoxinmentioning
confidence: 99%
“…These findings raise the question of whether C. curvispora, R. curvata and R. mediterranea can be regarded as separate species or are most likely just rare morphotypes of C. raciborskii. Strains of Cylindrospermopsis and Raphidiopsis from Australia, Brazil, China, Japan and Thailand produce CYN, STXs or ATX (Hawkins et al 1997;Saker and Neilan 2001;Li et al 2001;Namikoshi et al 2003;Soto-Liebe et al 2010). However, all the Cylindrospermopsis and Raphidiopsis strains isolated from Hartbeespoort Dam tested negative for production of cyanotoxins and their encoding genes.…”
Section: R Curvata From Hartbeespoort Dam Than To Cylindrospermopsismentioning
confidence: 99%